Signaling Required for Blood Vessel Maintenance: Molecular Basis and Pathological Manifestations - Masahiro Murakami (International Journal of Vascular Medicine)
As our understanding of molecular mechanisms leading to vascular formation increases, vessel maintenance including stabilization of new vessels and prevention of vessel regression began to be considered as an active process that requires specific cellular signaling. While signaling pathways such as VEGF, FGF, and angiopoietin-Tie2 are important for endothelial cell survival and junction stabilization, PDGF and TGF-β signaling modify mural cell (vascular smooth muscle cells and pericytes) functions, thus they fortify vessel integrity. Breakdown of these signaling systems results in pathological hyperpermeability and/or genetic vascular abnormalities such as vascular malformations, ultimately progressing to hemorrhage and edema. Hence, blood vessel maintenance is fundamental to controlling vascular homeostasis and tissue functions. This paper discusses signaling pathways essential for vascular maintenance and clinical conditions caused by deterioration of vessel integrity.